Attendance Registration Agency Employees Empower Women, Child Protection and Family Planning - Dovi Septiari; Nisa Fakhriatul Filzah (Journal of Applied Accounting and Taxation, 2016)
Women Empowerment, Child Protection and Family Planning do not have sufficient attendance, it is seen from the problems that occur in the institution. The problem is that the manual attendance recording can cause the presence of data manipulation, recording attendance is usually carried out by the foreman and supervised by the head of the production in order to avoid manipulation of attendance data. Based on research conducted by the authors of recording employee attendance BP3AKB Batam, the results obtained are employee attendance data collection process manually is quite difficult. Part staffing should note and record employee attendance manually which takes a lot, not effective because it uses a lot of paper. Vulnerable fraud or manipulation of attendance data. Possible solutions to the problems that occur in the institution is replacing of absent manually into finger print, ID barcode and other systems, increased waste paper and automatic budget spent for the purchase of paper also grew, forming part which oversees attendance and absences are placed near with the regulatory body to prevent further fraud.